Religious liberties anti-Catholicism and liberal democracy in nineteenth-century U.S. literature and culture - Fenton, Elizabeth A., 1978- (New York ; Oxford : Oxford University Press, 2011)
Early U.S. literary & cultural productions often presented Catholicism as a threat not only to Protestantism but also to democracy. Religious Liberties shows that U.S. understandings of religious freedom & pluralism emerged, paradoxically, out of a virulent anti-Catholicism.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: American literature -- 19th century -- History and criticism; Cultural pluralism in literature; Anti-Catholicism in literature; Religion and literature -- United States -- History -- 19th century; Liberalism in literature; Democracy in literature